Preparation method and application of graphene-like material

By preparing the combination of LDH materials with high adsorption properties and waste dyes, and obtaining graphene-like materials through high-temperature carbonization treatment, the problem of adsorption waste treatment and the problem of high graphene preparation cost are solved, and the efficient utilization of materials and environmentally friendly production process is achieved.

CN119565568APending Publication Date: 2025-03-07CHONGQING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901795.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively process and reuse LDH materials after adsorbing dyes, and the preparation process of graphene materials is complex, costly and severe environmental pollution.

Method used

By preparing MgAl-LDH and carrying out hydrothermal reaction in aqueous solution of hydrochloric acid and NaCl, a high adsorption performance LDH material was obtained. Then, the material is stirred and adsorbed with the waste dye containing carbon and nitrogen, and then carbonized at high temperature in a nitrogen atmosphere, and finally the graphene-like material is obtained by hydrothermal and drying treatment.

Benefits of technology

The effective utilization of adsorbed waste is achieved, the preparation cost and environmental pollution of graphene materials are reduced, and the obtained graphene-like materials can be used as negative electrode materials of supercapacitors, with excellent rate performance and good cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565568A_ABST
    Figure CN119565568A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a graphene-like material, and belongs to the field of new materials. According to the preparation method, carbon and nitrogen element materials in the dye are utilized, the pollution problem of the dye is solved, a novel process for preparing the graphene-like material is further provided, (1) magnesium salt, aluminum salt and hexamethylenetetramine serve as raw materials to prepare magnesium aluminum-layered double hydroxides (LDH), and the adsorption performance of the magnesium aluminum-layered double hydroxides (LDH) is improved through treatment of hydrochloric acid and a NaCl aqueous solution; (2) adsorbing the waste dye containing carbon and nitrogen elements by taking LDH as an adsorbent, and then carrying out high-temperature reaction in a nitrogen atmosphere to obtain a carbon-containing layered bimetal oxide (LDO-C); and (3) taking out the carbon material from the LDO through hydrochloric acid hydro-thermal treatment to obtain the graphene-like material. The method has the advantages of easily available raw materials and simple process, and realizes effective utilization of wastes. The obtained graphene-like material can be used as a capacitor negative electrode material and has excellent electrochemical performance. According to the invention, the preparation cost of the graphene material is reduced, the resource utilization rate is increased, the pollution is reduced, and the win-win situation of economic and environmental benefits is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new materials and relates to a preparation method and application of graphene-like materials. Background Art

[0002] Dyes are important raw materials in fine chemicals and have a wide range of applications. Most dyes are toxic and may cause serious harm to humans, animals and plants when discharged into the aquatic environment. Dye molecules have a stable molecular structure, and natural degradation is difficult and slow. At present, the treatment of dye pollutants in water bodies mainly uses adsorption methods. Using adsorbents, dye molecules in water can be quickly separated, thereby achieving the effect of water purification. However, the use of adsorbents will generate adsorbed waste. Current research mainly focuses on the adsorption and extraction of dye molecules, while ignoring the treatment and reuse of adsorbed waste, and related research is very weak. LDH is a layered material with exchangeable anions between layers. Through ion exchange, LDH can be used as an adsorbent for anionic dyes. The type of anions between LDH layers has a significant effect on the dye adsorption performance. However, current research has not reported how to treat LDH after adsorbing dyes. Currently known treatment methods such as landfill and decomposition not only have low economic value, but also require additional treatment costs. In the context of dual carbon, it is very necessary to develop methods for the conversion and reuse of adsorbed waste.

[0003] Graphene, a two-dimensional material composed of a single layer of carbon atoms tightly arranged in a hexagonal lattice, has unique chemical and physical properties and can be used in electronics, material strength, energy production, biomedicine and other fields. However, the preparation of graphene requires peeling off the graphite layer by layer. This process is very complicated and requires a series of harsh conditions and the support of high-tech equipment, which greatly increases the technical difficulty and equipment cost. In addition, in this process, reagents such as potassium permanganate, concentrated sulfuric acid, hydrogen peroxide, and hydrochloric acid are needed, which can easily cause serious pollution to the environment. Under the concept of green development that the country adheres to, it is urgent to prepare a new type of carbon material that can match the properties of graphene and reduce the preparation cost and environmental pollution to a certain extent. Summary of the invention

[0004] In view of this, one of the objects of the present invention is to provide a method for preparing a graphene-like material, and the second object is to use the obtained graphene-like material as a capacitor negative electrode material for the preparation of a capacitor.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a graphene-like material, and the preparation method comprises the following steps:

[0007] S1: preparing MgAl-LDH: dispersing magnesium salt, aluminum salt and hexamethylenetetramine in an aqueous solution, and reacting at 120-160° C. for 4-8 hours to obtain the MgAl-LDH;

[0008] S2: preparing a LDH material with high adsorption performance (LDH-1): placing the MgAl-LDH described in step S1 in an aqueous solution of hydrochloric acid and NaCl, and reacting at a temperature of 100° C. for 12 hours to obtain a precipitate product in the solution, which is the LDH-1 material with high adsorption performance;

[0009] S3: preparing graphene-like materials: adding the LDH-1 material with high adsorption performance in step S2 to the waste dye containing carbon and nitrogen elements for stirring and adsorption, then placing it in a nitrogen atmosphere at 800°C for 3 hours to obtain a reaction product LDO-C, placing the product in hydrochloric acid, hydrothermally treating at 120°C for 12 hours, and obtaining the graphene-like material after centrifugation, filtration, and vacuum freeze drying.

[0010] The molar mass ratio of the magnesium salt, the aluminum salt and the hexamethylenetetramine is 1.5:1.5:3, mmol:mmol:mmol.

[0011] The magnesium salt in step S1 is any one or more of magnesium carbonate, magnesium chloride or magnesium hydroxide;

[0012] The aluminum salt is any one or more of aluminum chloride, aluminum sulfate, aluminum nitrate or aluminum sulfide.

[0013] The waste dye containing carbon and nitrogen elements is a methyl orange solution,

[0014] The mass ratio of the MgAl-LDH material to NaCl in step S2 is 1:6.

[0015] The hydrochloric acid concentration is 0.5-12 mol / L,

[0016] The mass volume ratio of hydrochloric acid to water in the hydrochloric acid aqueous solution is 65:35, μL:mL.

[0017] Furthermore, a supercapacitor negative electrode material prepared by the graphene-like material prepared by the preparation method is

[0018] Furthermore, a supercapacitor is prepared using the graphene-like material supercapacitor negative electrode material.

[0019] The beneficial effects of the present invention are:

[0020] The raw materials of the present invention are easily available, the process is simple, and the waste is effectively utilized. The obtained graphene-like material can be used as a capacitor negative electrode material and applied to the preparation of supercapacitors, showing good application prospects. The present invention not only reduces the preparation cost of graphene materials, but also improves resource utilization, reduces environmental pollution, achieves a win-win situation of economic benefits and environmental benefits, and is of great significance to promoting the large-scale application of graphene materials.

[0021] The present invention converts LDH after dye adsorption into a new type of carbon material comparable to graphene. By controlling the influence of high-temperature carbonization temperature, carbonization time, and post-treatment process and drying conditions on the structure and performance of the prepared carbon material, a graphene-like carbon material is finally obtained. Through this technical means, while ensuring its excellent chemical properties and physical properties, its preparation cost and pollution to the environment are reduced, making it have significant economic value and social benefits. The successful implementation of the present invention can not only provide a new resource utilization approach for dye wastewater treatment, but also promote the application and development of carbon materials in multiple fields, which has important scientific value and practical significance.

[0022] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be described in detail below in conjunction with the accompanying drawings:

[0024] Figure 1 This is a scanning electron microscope image of the graphene-like supercapacitor negative electrode material in Example 1;

[0025] Figure 2 is the X-ray diffraction spectrum of the graphene-like supercapacitor negative electrode material in Example 1;

[0026] Figure 3 The graphene-like supercapacitor negative electrode material in Example 1 was respectively subjected to a scanning rate of 10 mVs -1 , 20mVs -1 、30mVs -1 , 40mVs -1 and 50mVs -1 Cyclic voltammetry curves below;

[0027] Figure 4The constant current charge and discharge curves of the graphene-like supercapacitor negative electrode material in Example 1 at current densities of 1A / g, 3A / g, 5A / g, 7A / g, and 10A / g, respectively;

[0028] Figure 5 is a scanning electron microscope image of the corresponding material in Comparative Example 1;

[0029] Figure 6 The corresponding materials in Comparative Example 1 were respectively at a scanning rate of 10 mVs -1 , 20mVs -1 、30mVs -1 , 40mVs -1 and 50mVs -1 Cyclic voltammetry curves below;

[0030] Figure 7 The constant current charge-discharge curves of the corresponding materials in Comparative Example 1 at current densities of 1A / g, 3A / g, 5A / g, 7A / g, and 10A / g, respectively;

[0031] Figure 8 It is the scanning electron microscope image of the corresponding material in Comparative Example 2;

[0032] Fig. 9 The corresponding materials in Comparative Example 2 were respectively at a scan rate of 10 mVs -1 , 20mVs -1 、30mVs -1 , 40mVs -1 and 50mVs -1 Cyclic voltammetry curves below;

[0033] Fig.10 It is a constant current charge and discharge curve diagram of the corresponding material in Comparative Example 2 at current densities of 1A / g, 3A / g, 5A / g, 7A / g, and 10A / g;

[0034] Fig.11 It is a comparison chart of the rate performance of corresponding materials in Example 1, Comparative Example 1 and Comparative Example 2;

[0035] Fig.12 TEM image of the prepared graphene-like material. DETAILED DESCRIPTION

[0036] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0037] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0038] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0039] Example 1

[0040] A method for preparing graphene-like materials based on adsorption of waste:

[0041] (1) Preparation of MgAl-LDH: A divalent water-soluble magnesium salt, a divalent water-soluble aluminum salt, and hexamethylenetetramine are dispersed in a solvent, and then reacted at 120 to 160° C. for 4 to 8 hours to obtain a solid-liquid mixture. The solid-liquid mixture is centrifuged, filtered, washed with water, and then dried for more than 24 hours to obtain MgAl-LDH.

[0042] (2) Preparation of LDH material with high adsorption performance: The MgAl-LDH in step (1) is placed in an aqueous solution of 12 mol / L hydrochloric acid and NaCl, and hydrothermally heated at 100°C for 12 hours to obtain a precipitated product in the solution. The product is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the solid product is obtained by repeatedly washing with boiled and cooled pure water and centrifuging 4 to 6 times, and then a precipitated solid product is obtained, and a methyl orange aqueous solution is prepared, wherein the volume mass ratio of methyl orange to pure water in the solution is 2:400, mg:ml. The above-mentioned precipitated solid product is placed in the methyl orange aqueous solution and stirred and adsorbed for 1 hour to obtain a solid-liquid mixture. The above-mentioned solid-liquid mixture is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the pure water is also repeatedly washed with boiled and cooled pure water and centrifuged 4 to 6 times, and then placed in a 60°C oven for drying for more than 12 hours to obtain a LDH material (LDH-1) with high adsorption performance.

[0043] (3) Preparation of graphene-like material: The LDH material with high adsorption performance described in step (2) is placed in a nitrogen atmosphere and reacted at 800° C. for 3 h to obtain a reaction product LDO-C, the product is placed in 12 mol / L hydrochloric acid and hydrothermal at 120° C. for 12 h, then placed in a centrifuge tube and centrifuged at 10,000 rpm for 7 min, the upper light liquid is filtered out, and the water washing and centrifugation are repeated 4 to 6 times, and then vacuum dried in a freeze dryer for 15 to 16 h to obtain a graphene-like material.

[0044] like Fig.12 This is a TEM image of a graphene-like material. From a microscopic perspective, due to the confinement effect of LDH on graphene-like materials, the growth of graphene-like materials is confined to the layer space of LDH. Therefore, the obtained material inherits the basic structure of LDH and is in the shape of hexagonal nanosheets. Figure 1 From the results, we can see that the graphene-like particles aggregated together have the morphology of nanoflowers composed of loose nanosheets, which is very similar to graphene in morphology.

[0045] Comparative Example 1

[0046] A supercapacitor negative electrode material, the specific preparation method of which is as follows:

[0047] (1) Preparation of MgAl-LDH: A divalent water-soluble magnesium salt, a divalent water-soluble aluminum salt, and hexamethylenetetramine are dispersed in a solvent, and then reacted at 120 to 160° C. for 4 to 8 hours to obtain a solid-liquid mixture. The solid-liquid mixture is centrifuged, filtered, washed with water, and then dried for more than 24 hours to obtain MgAl-LDH.

[0048] (2) Preparation of LDH material with high adsorption performance: The MgAl-LDH in step (1) is placed in an aqueous solution of 12 mol / L hydrochloric acid and NaCl, and hydrothermally heated at 100°C for 12 hours to obtain a precipitated product in the solution. The product is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the solid product is obtained by repeatedly washing with boiled and cooled pure water and centrifuging 4 to 6 times, and then a precipitated solid product is obtained, and a methyl orange aqueous solution is prepared, wherein the volume mass ratio of methyl orange to pure water in the solution is 2:400, mg:ml. The above-mentioned precipitated solid product is placed in the methyl orange aqueous solution and stirred and adsorbed for 1 hour to obtain a solid-liquid mixture. The above-mentioned solid-liquid mixture is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the water is washed and centrifuged with boiled and cooled pure water for 4 to 6 times, and then placed in a 60°C oven for drying for more than 12 hours to obtain a LDH material with high adsorption performance.

[0049] (3) Preparation of graphene-like material: The LDH material with high adsorption performance described in step (2) is placed in a nitrogen atmosphere and reacted at 700° C. for 3 h to obtain a reaction product LDO-C, the product is placed in 12 mol / L hydrochloric acid and hydrothermal at 120° C. for 12 h, then placed in a centrifuge tube and centrifuged at 10,000 rpm for 7 min, the upper light liquid is filtered out, and the water washing and centrifugation are repeated 4 to 6 times, and then vacuum dried in a freeze dryer for 15 to 16 h to obtain a supercapacitor negative electrode material.

[0050] Comparative Example 2

[0051] A supercapacitor negative electrode material, the specific preparation method of which is as follows:

[0052] (1) Preparation of MgAl-LDH: A divalent water-soluble magnesium salt, a divalent water-soluble aluminum salt, and hexamethylenetetramine are dispersed in a solvent, and then reacted at 120 to 160° C. for 4 to 8 hours to obtain a solid-liquid mixture. The solid-liquid mixture is centrifuged, filtered, washed with water, and then dried for more than 24 hours to obtain MgAl-LDH.

[0053] (2) Preparation of LDH material with high adsorption performance: The MgAl-LDH in step (1) is placed in an aqueous solution of 12 mol / L hydrochloric acid and NaCl, and hydrothermally heated at 100°C for 12 hours to obtain a precipitated product in the solution. The product is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the solid product is obtained by repeatedly washing with boiled and cooled pure water and centrifuging 4 to 6 times, and then a precipitated solid product is obtained, and a methyl orange aqueous solution is prepared, wherein the volume mass ratio of methyl orange to pure water in the solution is 2:400, mg:ml. The above-mentioned precipitated solid product is placed in the methyl orange aqueous solution and stirred and adsorbed for 1 hour to obtain a solid-liquid mixture. The above-mentioned solid-liquid mixture is placed in a centrifuge tube and centrifuged at 5000 rpm for 3 minutes, the upper light liquid is filtered out, and the water is washed and centrifuged with boiled and cooled pure water for 4 to 6 times, and then placed in a 60°C oven for drying for more than 12 hours to obtain a LDH material with high adsorption performance.

[0054] (3) Preparation of graphene-like material: The LDH material with high adsorption performance described in step (2) is placed in a nitrogen atmosphere and reacted at 900° C. for 3 h to obtain a reaction product LDO-C, the product is placed in 12 mol / L hydrochloric acid and hydrothermal at 120° C. for 12 h, placed in a centrifuge tube and centrifuged at 10,000 rpm for 7 min, the upper light liquid is filtered out, and the water washing and centrifugation are repeated 4 to 6 times, and then vacuum dried in a freeze dryer for 15 to 16 h to obtain a supercapacitor negative electrode material.

[0055] Example 2 Performance Test

[0056] (1) The graphene-like supercapacitor negative electrode material prepared based on adsorbed waste in Example 1 was tested by scanning electron microscopy.

[0057] The results of the scanning electron microscope test of the graphene-like supercapacitor negative electrode material prepared based on adsorption of waste in Example 1 are as follows: Figure 1 As shown. Figure 1 It can be seen that the material has good morphology, large specific surface area, and obvious layered flake structure distribution, indicating that the material has good electrical conductivity. It can be expected that the material has excellent rate performance.

[0058] (2) Cyclic voltammetry curves of the graphene-like supercapacitor negative electrode material prepared based on adsorbed waste in Example 1 were tested at different scanning speeds.

[0059] The graphene-like supercapacitor negative electrode material prepared based on adsorption of waste in Example 1 was plotted at a scan rate of 10 mVs -1 , 20mVs -1 、30mVs -1 , 40mVs -1 and 50mVs -1The cyclic voltammetry curve below shows the experimental results. Figure 3 As shown. Figure 3 It can be seen that the symmetry and shape of the cyclic voltammetry curve are stable, which shows that the prepared material has high purity and good stability.

[0060] (3) The graphene-like supercapacitor negative electrode material prepared based on adsorbed waste in Example 1 was tested for constant current charge and discharge curves at different current densities.

[0061] The constant current charge and discharge curves of the graphene-like supercapacitor negative electrode material prepared based on adsorption of waste in Example 1 at 1A / g, 3A / g, 5A / g, 7A / g, and 10A / g were plotted respectively. The experimental results are shown in Figure 4 As shown. Figure 4 It can be seen that with the increase of current density, the shape of the charge and discharge curve does not change significantly. This shows that the structure of the material is not destroyed and the conductivity of the material is good, which further shows that the material has very good rate performance.

[0062] (4) Comparative Example 1 and Comparative Example 2 show the electrochemical properties of the corresponding materials.

[0063] In order to intuitively reflect the high performance of the graphene-like supercapacitor negative electrode material prepared based on waste adsorption in this application, the electrochemical performance of the material is compared with that of other materials, and the materials of Comparative Example 1 and Comparative Example 2 are plotted at a scan rate of 10 mVs -1 , 20mVs -1 、30mVs -1 , 40mVs -1 and 50mVs -1 The cyclic voltammetry curves under Figure 5 and Figure 8 ), constant current charge and discharge curves at current densities of 1A / g, 3A / g, 5A / g, 7A / g, and 10A / g (respectively Figure 6 and Fig. 9 ) and rate performance diagram ( Fig.10 ). Combined Figure 5 , Figure 6 , Figure 8 ,and Fig. 9It can be seen that the material in the embodiment has a capacitance performance of 198.9F / g at a current density of 1A / g; at a current density of 10A / g, it can still maintain 76.49% of the capacitance performance; however, the material in comparative example 1 has a capacitance performance of only 183.9F / g at a current density of 1A / g; at a current density of 10A / g, it can maintain 31.14% of the capacitance performance; the material in comparative example 2 has a capacitance performance of only 137.2F / g at a current density of 1A / g; at a current density of 10A / g, it can only maintain 32.14% of the capacitance performance.

[0064] In summary, the present invention provides a graphene-like supercapacitor negative electrode material prepared based on adsorbed waste, which has excellent rate performance and good cycle performance.

[0065] The present invention also provides a method for preparing graphene-like supercapacitor negative electrode materials based on adsorbed waste. The method mainly uses a hydrothermal method or a solvent thermal method and high-temperature calcination, has a simple device, is easy to operate, has low raw material costs, and is easy to mass produce.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a graphene-like material, characterized in that: The preparation method steps are as follows: S1: preparing MgAl-LDH: dispersing magnesium salt, aluminum salt and hexamethylenetetramine in an aqueous solution, and reacting at 120-160° C. for 4-8 hours to obtain the MgAl-LDH; S2: preparing a LDH material with high adsorption performance (LDH-1): placing the MgAl-LDH described in step S1 in an aqueous solution of hydrochloric acid and NaCl, and reacting at a temperature of 100° C. for 12 hours to obtain a precipitate product in the solution, which is the LDH-1 material with high adsorption performance; S3: Preparation of graphene-like material: adding the LDH-1 material with high adsorption performance in step S2 to the waste dye containing carbon and nitrogen elements and stirring for adsorption, then placing it in a nitrogen atmosphere at 800°C for reaction for 3 hours to obtain the reaction product LDO-C, placing the product in hydrochloric acid, hydrothermally treating it at 120°C for 12 hours, and obtaining the graphene-like material after centrifugation, filtration, and vacuum freeze-drying.

2. The method for preparing a graphene-like material according to claim 1, characterized in that: The molar mass ratio of the magnesium salt, the aluminum salt and the hexamethylenetetramine is 1.5:1.5:3, mmol:mmol:mmol.

3. The method for preparing a graphene-like material according to claim 2, characterized in that: The magnesium salt described in step S1 is any one or more of magnesium carbonate, magnesium chloride or magnesium hydroxide; the aluminum salt is any one or more of aluminum chloride, aluminum sulfate, aluminum nitrate or aluminum sulfide.

4. The method for preparing a graphene-like material according to claim 3, characterized in that: The waste dye containing carbon and nitrogen elements is a methyl orange solution.

5. The method for preparing a graphene-like material according to claim 4, characterized in that: The mass ratio of the MgAl-LDH material to NaCl in step S2 is 1:

6.

6. The method for preparing a graphene-like material according to claim 5, characterized in that: The concentration of the hydrochloric acid is 0.5-12 mol / L.

7. The method for preparing a graphene-like material according to claim 6, characterized in that: The mass volume ratio of hydrochloric acid to water in the hydrochloric acid aqueous solution is 65:35, μL:mL.

8. A supercapacitor negative electrode material prepared from a graphene-like material prepared by the preparation method according to any one of claims 1 to 7.

9. A supercapacitor prepared from the graphene-like supercapacitor negative electrode material according to claim 8.